1987
DOI: 10.1677/joe.0.1120139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing and hormonal manipulations on the level of oestrogen receptors in the guinea-pig prostate

Abstract: Cytosolic oestrogen receptor levels in guinea-pig prostate tissue were found to decrease with increasing age, irrespective of whether the binding was expressed relative to cytosolic protein or cellular DNA. This decrease in oestrogen receptor levels was also observed using enriched fibromuscular stromal tissue prepared by mechanical fractionation of the prostate. The most pronounced change in cytosolic oestrogen receptor levels (from 133 to 35 fmol/mg protein) occurred at the onset of puberty. The pubertal dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Previously, we have shown that guinea pig prostate estrogen receptor levels decrease more than threefold during pubertal development [8]. This decrease was observed irrespective of whether the binding was expressed relative to cytosolic protein or cellular DNA.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previously, we have shown that guinea pig prostate estrogen receptor levels decrease more than threefold during pubertal development [8]. This decrease was observed irrespective of whether the binding was expressed relative to cytosolic protein or cellular DNA.…”
Section: Discussionmentioning
confidence: 74%
“…Male guinea pigs (IMVS coloured; outbred strain) were purchased from the Institute of Medical and Veterinary Sciences (Adelaide, Australia) and maintained on a standard diet under conditions of regular lighting and constant temperature for at least 1 week prior to use. Animals were classified as prepubertal (body weight <230 g), pubertal (230-500 g), postpubertal (501-800 g), or mature (>go0 g) as previously described [8]. Castration was performed under nembutal anesthesia (25 pgikg).…”
Section: Animals and Tissuesmentioning
confidence: 99%
“…Oestrogens have been shown to promote BDNF synthesis in many brain regions (Sohrabji et al 1995;Gibbs 1998;Jazierski and Sohrabji 2000;Liu et al 2001;Solum and Handa 2002) and in the uterus (Krizsan-Agbas et al 2003). In addition, castration has been demonstrated to induce an increase of oestrogen receptor levels in the fibromuscular stroma of prostate and vesicular gland (Tilley et al 1987;Bodker et al 1994;Yuasa et al 1997;West et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodent prostate glands have shown a relatively high percentage of stromal cells express ERα mRNA and protein during perinatal morphogenesis and this proportion significantly declines thereafter suggesting a specific role for ERα in prostate development [73,75,76]. A decline in expression with puberty suggests that androgens may normally suppress ERα expression, a finding that has been borne out in direct studies [77,78]. In humans, ERα has been consistently observed in stromal cells during fetal development [79].…”
Section: Erαmentioning
confidence: 99%